2019
DOI: 10.3390/ijms20061498
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tyrosine Phosphorylation of Protein Kinase C Delta in Infection and Inflammation

Abstract: Protein Kinase C (PKC) is a family composed of phospholipid-dependent serine/threonine kinases that are master regulators of inflammatory signaling. The activity of different PKCs is context-sensitive and these kinases can be positive or negative regulators of signaling pathways. The delta isoform (PKCδ) is a critical regulator of the inflammatory response in cancer, diabetes, ischemic heart disease, and neurodegenerative diseases. Recent studies implicate PKCδ as an important regulator of the inflammatory res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 131 publications
3
37
0
Order By: Relevance
“…In addition, neutrophil adhesion, which is crucial to migration, was enhanced by LPS stimulation. During sepsis, increasing the adhesion of neutrophils leads to enhanced interactions between neutrophils and endothelial cells followed by vascular endothelial injury and organ dysfunction (26). Our results demonstrated that AMP treatment reduced adhesion and that this effect was A1R-dependent.…”
Section: Discussionsupporting
confidence: 51%
“…In addition, neutrophil adhesion, which is crucial to migration, was enhanced by LPS stimulation. During sepsis, increasing the adhesion of neutrophils leads to enhanced interactions between neutrophils and endothelial cells followed by vascular endothelial injury and organ dysfunction (26). Our results demonstrated that AMP treatment reduced adhesion and that this effect was A1R-dependent.…”
Section: Discussionsupporting
confidence: 51%
“…PKCδ localizes to multiple subcellular sites including the plasma membrane, cytoplasm, and nucleus, with localization impacted by its activation status [ 29 ]. PKCδ acquires activating phosphorylation marks during influenza virus infection [ 27 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…To effectively respond to environmental antigens, the immune system is exquisitely balanced 63 . PTMs, such as phosphorylation, help to ensure the balance of immune signal transduction by activating or terminating the immune responses at the proper time 64 . In our study, GO analysis showed that 183 phosphorylated proteins belonging to the ‘immune system process’ term.…”
Section: Discussionmentioning
confidence: 99%